Effect of heavy dynamic resistive exercise on acute upper-body power - Hrysomallis, C.; Kidgell, D. (The Journal of Strength and Conditioning Research, 2001)
There is limited research to support the notion that heavy resistive exercise immediately before a power movement may acutely enhance performance. Upper-body acute power enhancement during a stretch-shorten cycle (SSC) movement has not been previously investigated. The aim of this project was to determine whether a set of 5 repetitions of 5 repetition maximum (RM) bench press preceding explosive push-ups would significantly influence indicators of power: impulse and maximum rate of force development. Subjects randomly performed either explosive push-ups only over a force platform or a set of 5RM bench press before the explosive push-ups. There were no significant differences for any of the force platform data when the explosive push-ups were preceded by a set of 5RM bench press. It appears that heavy dynamic resistive upper-body exercise on its own before an upper-body power activity is inadequate in augmenting short-term power.